Infectious Eye Diseases Recent Advances in Diagnosis and Treatment - Rodriguez-Garcia, Alejandro; Hernandez-Camarena, Julio C. (IntechOpen, 2021)
Infectious eye disorders represent one of the most feared, sight-threatening, and challenging clinical ocular conditions. Visual loss due to eye infection significantly impacts patients' productivity and quality of life. The development of accurate diagnostic tests and better treatment alternatives results from intensive and innovative medical research committed to improving the standard of care of patients suffering from these blinding diseases. This book focuses on the most recent advances in diagnostic techniques for common infectious disorders, including viral, fungal, and contact lens-related keratitis, infectious uveitis, endophthalmitis, and COVID-19-related eye infection. It also describes the current therapeutic strategies that significantly reduce the rate of ocular complications and improve the visual outcome of patients suffering from such devastating disorders.